High-value data product and analytic pipeline demonstrating value of Open and FAIR data: enabling researchers to assess climate risk profiles and crop suitability at national scale. - CGIAR Platform for Big Data in Agriculture (2020)
Models finalized, analyses complete, sixteen country reports being finalized.